Analysis Of Business Implementation on Shopeepay Digital Wallet using Business Model Canvas (BMC) and Swot Analysis - Nella Aginta Pinem; Fifi Sulistyawati; Eirene Nifati Pangkey Gulo (Riviera Publishing, 2023)
Introduction: E-payment, or electronic payment, is a type of payment used when shopping. The financial industry has revolutionized and transformed into an ergonomic method of utility, accessibility, convenience and cost. E-Payment or Electronic payments include bank transfers, e-wallets, QR codes, Paypal and Credit Cards, but researchers examine more deeply electronic payments using e-wallets. Method: This research uses a qualitative descriptive method with a Business Model Canvas approach that uses secondary data, namely data collection through literature studies, journals, books, and websites that are trusted. Results: The first step in this research is to map the current ShopeePay canvas business model. In the business model canvas, observations and considerations are formulated to formulate a business strategy. From this research, several alternative BMC improvement strategies and operational development of the ShopeePay application have been obtained in each component of the canvas model activity block. Conclusion: The results of this study indicate that the ShopeePay business model needs to be improved. The company's business model must be evaluated and followed by technological developments; Fintech is a dynamic industry because it follows the evolution of technology. Therefore, it is necessary to change the elements contained in the nine elements of Canva's business model, such as key partners, key activities, value propositions, customer relationships, channels, customer segments, cost structure, and revenue stream elements.